Analysis of the Relationship between Fine Motor Skills and Montage Activities in Early Childhood - Slamet Riyadi; Muhammad Darwis; Tukiyo; Mas’ud Muhammadiah; Didik Cahyono (Journal of Childhood Development, 2023)
This study aimed to determine the fine motor skills of kindergarten children through montage activities. The method used in this study is pre-experimental with a one-group pretest-posttest design. The subjects in this study were children aged 5–6 years. The study involved all children, consisting of 8 children. In this study, all children participated in the pre-test to determine the initial condition of fine motor skills, then were given treatment using montage activities. A post-test was conducted to determine the final condition of the children before and after being given treatment. The data collection techniques used are observation, documentation, and tests. The data obtained is in the form of scores and is then processed using statistical methods. The data analysis techniques used in this research are the normality test and the t-test. It is proven that montage activities affect children's fine motor skills based on the paired sample t-test with a significance level of 0.05.